Effect of different fish meal on growth performance, apparent and partial digestibility coefficient of Atlantic Salmon (Salmo salar) - Muhammad Ahmad Rana 1996- (2025)
Fish meal is a key protein source in aquaculture feeds due to its high nutritional value and digestibility. However, variations in fish meal composition may affect nutrient availability and fish growth performance. This study aimed to assess whether different fish meal exhibit variations in digestibility and their impact on the growth of post-smolt Atlantic salmon (Salmo salar). A six-week feeding trial was conducted at Matís Aquaculture Research Station (MARS) in Reykjavík, Iceland, using six experimental diets (A, B, C, D, E, and F) formulated with different industry-sourced fish meal. Growth performance was evaluated by measuring specific growth rate (SGR) and feed conversion ratio (FCR), while digestibility was assessed through apparent digestibility coefficients (ADC) and partial digestibility estimates for crude protein and key amino acids (cysteine, lysine, threonine, methionine, and valine). Nutrient composition was similar across fish meal, except for feed B, which contained higher protein and amino acid levels. No significant differences were observed in SGR, FCR, or ADCs. However, partial digestibility of cysteine was significantly higher in feeds F (78.26 ± 7.05) and B (74.12 ± 10.03) compared to feed E (48.59 ± 22.04). Fish fed diet D showed a trend toward higher final weights (61.76% ± 2.18), whereas those fed diet A exhibited the lowest weight gain (55.88% ± 2.49). These results suggest that while some differences in amino acid digestibility exist among fish meal, overall growth performance remains relatively unaffected. Closed until February 2050